Optimization of Logistics Processes in Domestic Road Transport - Tumielewicz, Michał; Libich, Katarzyna (Towards Sustainable Transport in Logistics and International Trade, 2025)
The aim of this chapter is to present the functioning of logistics processes in freight forwarding and their impact on the transport efficiency of a company operating in the TSL sector. The study used a diagnostic survey method, employing a proprietary questionnaire directed at company employees. The results indicate that the organization of forwarding processes was assessed as good, although problems were identified in interdepartmental coordination and insufficient information flow. Moreover, despite the use of modern TMS tools, dissatisfaction with their integration was noted. The main barriers include infrastructure instability and delays by contractors. The research also shows potential for automation of logistics processes, which may contribute to improving service efficiency and quality. The study has practical significance for optimizing logistics processes in freight forwarding.